Microlithography and Metrology in Micromachining II 1996
DOI: 10.1117/12.250971
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures designed for shock robustness

Abstract: This research was performed to address the issue of shock robustness in silicon microstructures. The improvements were incorporated by considering features to reduce stress concentration and by geometries that have a more uniform stress distribution. The designs were evaluated by finite element models and by testing with wafer level techniques. The designs were intended to have the same fundamental frequency, inertia properties and damping properties. Six different designs were developed and distributed across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Li and Shemansky [14] observed through experimental drop tests of the MEMS accelerometers overlap failures between the moving parts and the stationary parts, which are caused by the large deflection of the moving parts during testing. Cunningham et al [15] investigated the effect of stress concentration on the robustness of silicon microstructures against shock.…”
Section: Introductionmentioning
confidence: 99%
“…Li and Shemansky [14] observed through experimental drop tests of the MEMS accelerometers overlap failures between the moving parts and the stationary parts, which are caused by the large deflection of the moving parts during testing. Cunningham et al [15] investigated the effect of stress concentration on the robustness of silicon microstructures against shock.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the deflection can be equal to the gap (typically 2jim) of the sacrificial layer, involving stiction phenomenon and impacts (fatigue). Cmmingham et al have addressed the issue of shock robustness in silicon microstructures [1]. They evaluated different microbeam designs and found that those with reduced stress distributions were more robust to the effects of shock.…”
Section: Introductionmentioning
confidence: 98%
“…4755 b. Large deflections domain1. Determination of the deflectionThis part is based on results displayed in[6], concerning large amplitudes of deflection.…”
mentioning
confidence: 99%
“…Several works have been based on finite-element models, for example Cunningham et al [10], Wagner et al [11], Lim et al [12], Atwell et al [13], Jiang et al [14], Fan and Shaw [15], and Mariani et al [16,17]. Other researchers modeled the shock problem of MEMS using lumped spring-mass-damper models, such as Srikar and Senturia [18], Li and Shemansky [6], Qian et al [19], Coster et al [20], Bao et al [21], Khatami and Rezazadeh [22], and Ghisi et al [23].…”
Section: Introductionmentioning
confidence: 99%